Lactation performances in primiparous Holstein cows following short and normal gestation lengths - Probo, Monica; Atashi, Hadi; Hostens, Miel (Frontiers in Veterinary Science, 2024)
The aim of this study was to compare the lactation performances in primiparous Holstein cows after a short gestation length (GL) or abortion to those after a normal GL. The data were collected using an automated data collection system. The 94 herds evaluated were located in Belgium, France, Italy, the Netherlands and Germany. Data from a wide range of physiological cow-life events including birth and calving events, reproduction events (insemination, pregnancy checks, abortions), milking events were collected. The GL was defined as the interval between the last insemination and the subsequent calving (or abortion) within a range of 150-297 d. Animals were categorized into one of 5 categories based on GL quantiles (C-I to C-V). Lactation curve parameters including the scale, ramp and decay were estimated using the Milkbot model. Then, the derived 305-d milk yield (M305-d), peak yield, and time to peak were compared between different GL categories. Of 13,732 lactations, 15 (0.11%) were found with a GL shorter than 210 d (ranging from 158 to 208 d). The 305-d milk yield was significantly lower in the C-I (7,566±186) and C-II groups (7,802±136 kg), compared to the C-III (8,254±116 kg), C-IV (8,148±119 kg) and C-V (8,255±117 kg) groups. The same trends were found for the scale and peak yield of the lactation; the lowest scale were found for the C-I (31.5±0.73 and C-II (32.8±0.53) groups, and the highest were found for the C-III (34.5±0.46), C-IV (34.9±0.45) and C-V (35,0±0.45) groups. Peak yield increased significantly from C-I (27.8±0.66 kg) and C-II group (28.8±0.48 kg) to the C-III (30.2±0.42 kg) and further to the C-IV (30.6±0.40 kg) and C-V (30.6±0.41 kg) groups.Moreover, primiparous cows in the C-II GL category showed a higher milk yield persistency (decay of 1.30E-4±3.55E-5) compared to those belonging to the C-IV (decay of 1.38E-4±2.51E-5) and C-V (decay of 1.38E-4±2.58E-5) group. In conclusion, results showed that primiparous cows with a shorter GL produced significantly less 305-d milk and peak yields, had a higher lactation persistency, and showed a lower upward slope of the lactation curve compared to those with a normal GL.